STRATEGI KUALITAS PRODUK DAN LAYANAN UNTUK MENINGKATKAN KEPUASAN PELANGGAN LISA COSTUME - Tan, Michelle; Nastasya Cindy Hidajat (Jurnal Serina Abdimas, 2024)
The development of service businesses is increasing rapidly in the modern era, so business competition is getting tighter. Companies need to innovate by providing quality products at affordable and innovative prices according to market needs to attract customers. Customer decisions in ordering costumes are influenced by the quality of the products and services provided. Both of these play an important role in the success of a service business, attracting new customers, retaining them, and creating a competitive advantage. Customer satisfaction is the key to business success, because consumers will return if they are satisfied with the products and services offered. Costume rentals, such as Lisa Costume, are an interesting entrepreneurial project by providing various adult and children's costume themes for various events, such as fashion shows, art performances and other events. The method used is consultation, so that this PKM can run optimally and in a structured manner. Lisa Costume develops new products that follow trends, such as batik clothes and traditional clothes with a modern feel, recycled clothes, character costumes according to film developments, and various other costume innovations. The results of this PKM have an impact on increasing revenue, customer repeat orders, and better customer ratings. Creative and innovative marketing strategies, through Instagram and brochures, expand market share, increase customer satisfaction, retain old customers and attract the attention of new customers. Thus, it is hoped that the results of this research can provide recommendations for Lisa Costume in improving the quality of products and services to attract more customers. ABSTRAK Perkembangan bisnis jasa meningkat pesat di era modern, sehingga persaingan bisnis semakin ketat. Perusahaan perlu berinovasi dengan menyediakan produk berkualitas dengan harga terjangkau dan inovatif sesuai kebutuhan pasar untuk menarik pelanggan. Keputusan pelanggan dalam memesan kostum dipengaruhi oleh kualitas produk dan layanan yang diberikan. Kedua hal ini memainkan peran penting dalam kesuksesan bisnis jasa, menarik pelanggan baru, mempertahankan, dan menciptakan keunggulan kompetitif. Kepuasan pelanggan adalah kunci kesuksesan bisnis, karena konsumen akan kembali jika puas dengan produk dan layanan yang ditawarkan. Rental kostum, seperti Lisa Costume, menjadi proyek kewirausahaan yang menarik dengan menyediakan berbagai tema kostum dewasa dan anak-anak untuk berbagai acara, seperti lomba peragaan busana, pentas seni, dan acara lainnya. Metode yang dilakukan adalah konsultasi, sehingga PKM ini bisa berjalan dengan optimal dan terstruktur. Lisa Costume mengembangkan produk baru yang mengikuti tren, seperti baju batik dan baju adat dengan nuansa modern, baju daur ulang, kostum karakter sesuai perkembangan film, dan berbagai inovasi kostum lainnya. Hasil dari PKM ini berdampak pada peningkatan pendapatan, customer repeat order, dan penilaian pelanggan yang semakin baik. Strategi pemasaran yang kreatif dan inovatif, melalui Instagram dan brosur memperluas pangsa pasar, meningkatkan kepuasan pelanggan, mempertahankan pelanggan lama, dan menarik perhatian pelanggan baru. Dengan demikian, hasil dari penelitian ini diharapkan dapat memberikan rekomendasi bagi Lisa Costume dalam meningkatkan kualitas produk dan layanan untuk menarik lebih banyak pelanggan